Higher population genetic diversity within the algal symbiont Durusdinium in Pocillopora verrucosa from Mexican Pacific reefs correlates with higher resistance to bleaching after the El Niño 2015–16 event. (21st June 2021) - Cárdenas‐Alvarado, María Angeles; Nava, Héctor; González‐Rodríguez, Antonio; Maldonado‐López, Yurixhi; Rodríguez‐Lanetty, Mauricio
Abstract: Zooxanthellae are dinoflagellate algae belonging to the family Symbiodiniaceae that provide energy and oxygenation to corals, allowing them to develop a high calcification rate. Additionally, some species of these algal symbionts seem to be related to coral resistance to particular environmental conditions, and such responses have a high potential to cope with climate change and related phenomena. In this study, we examined the role of algal symbiont diversity in the resistance of corals to thermal stress along four coral reefs from the Mexican Pacific after the "El Niño" event of 2015–16. To assess the composition and genetic diversity of the populations of zooxanthellae, the 28S and ITS2 nrRNA genes were amplified and sequenced from a total of 102 fragments of Pocillopora verrucosa . The resulting phylogenetic trees of both molecular markers showed that all sequences were grouped within clade D corresponding to genus Durusdinium, closely related to the subtypes D1.1 and D1.2, respectively. The presence of this genus has been related to the ability of coral hosts to endure thermal stress. Analysis of haplotype networks showed a higher number of haplotypes for the ITS2 in comparison with the 28S marker, with 28 and 5 haplotypes, respectively. With the ITS2 marker, the haplotypes from Islote Zacatoso were differentiated with more mutational steps, showing the highest genetic diversity. This population was associated with corals that suffered a minimum coral bleaching during the El Niño event of 2015–16. Moreover, the population of Playa Las Gatas had the lowest genetic diversity in the area and showed the highest incidence of coral mortality and bleaching. In this way, we discuss the possible relationship between both local and external environmental conditions and current composition of zooxanthellae as modulators of the response of corals to thermal stress: higher genetic diversity of zooxanthellae seems to be related to high resistance to thermal stress.